2016
DOI: 10.1159/000449028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Scenario of the Metabolic Syndrome

Abstract: The term metabolic syndrome (MeS) refers to a cluster of associated symptoms composed of impaired fasting glucose, abdominal obesity, hypertension, and dyslipidemia. MeS is associated with an increased risk of cardiovascular and diabetes-associated morbidity and mortality. The increased amount of visceral fat together with a chronic inflammatory state predisposes to the development of arteriosclerosis. Furthermore, insulin resistance (IR) and dyslipidemia are associated with fatty liver disease. In addition, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…Metabolic syndrome (MetS) is a cluster of metabolic disorders and associated with obesity, insulin resistance, hypertension, and dyslipidemia, and it increases risks for cardiovascular diseases (CVDs) and type 2 diabetes mellitus (T2DM). [1][2][3][4][5] In the past decade, the prevalence of MetS has increased to 34.7% in USA, and to 24.5% in China. 6,7 MetS has led to a 1.5 to 2.5 fold increase in the mortality from CVD that makes a major public health problem today.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a cluster of metabolic disorders and associated with obesity, insulin resistance, hypertension, and dyslipidemia, and it increases risks for cardiovascular diseases (CVDs) and type 2 diabetes mellitus (T2DM). [1][2][3][4][5] In the past decade, the prevalence of MetS has increased to 34.7% in USA, and to 24.5% in China. 6,7 MetS has led to a 1.5 to 2.5 fold increase in the mortality from CVD that makes a major public health problem today.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results revealed that the most important factor that affects metabolic dysregulation in obesity is IR, which probably appears to be predominantly early stage of the Met-HO. There is evidence that an accumulation of visceral adiposity tissue (VAT) might associate with over-production of pro-inflammatory cytokines including hs-CRP, leptin and vistafin and induce IR (Brede et al, 2016). Therefore, infiltration of the sub-intima by LDL cholesterol may induce production of free radicals, oxidation of cytoskeleton and membrane vesiculation of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is detrimental to people because it comes with more disorders like an increase in breathing rate, an abnormal increase in heart rate, and increases in blood pressure disrupting the normal life of humans, making them un it. To de ine novel methods of avoidance and therapy, the pathogenesis of obesity is crucial (Brede, 2016).…”
Section: Pathogenesismentioning
confidence: 99%